Pengaruh Karakteristik Demografi terhadap Literasi Keuangan Masyarakat Kota Bengkulu - Rahmayanti, Dewi (MOTIVASI, 2017)
ABSTRACT Purpose - This study aims to examine how the demographic characteristics of the variable influence on financial literacy.Design/methodology - The method used in this research is descriptive and verification methods.Findings – The result show that A wide variety of characteristics of the respondents used to describe the level of financial literacy Bengkulu City community. High and low levels of financial literacy (financial knowledge) is determined by the relationship or interaction between the characteristics of age, gender, income level, marital status, and financial experience. Age is a variable very high influence low level of financial knowledge (financial knowledge). Variations in the rate of age will cause variations in the level of financial knowledge. The higher level of the person's age the higher the level of knowledge about finances.